Method for preparing cementing material from silicon-aluminum-based solid waste

By optimizing the mixed method of silicon-based-aluminum solid waste in the preparation of alkaline stimulation of gel materials, make full use of waste glass as a silicon-based solid waste, solve the problem that the waste glass has not fully played and the amount of recovery is small, and achieves high efficiency. The preparation of gel materials and improvement of material performance.

CN119371126AInactive Publication Date: 2025-01-28SHENZHEN CONSTR GRP +1

Patent Information

Application Number
CN202411341087.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, waste glass does not fully play its role as silicon-based solid waste when preparing alkali-exciting gelling materials, and the reuse amount is small.

Method used

By mixing the alkaline stimulation auxiliary powder and silicon -based solid waste, add water and stir until the active silicon dissolves, forming an alkaline stimulation of the front -drive body slurry, and then add a mixed solid waste of silicon -containing solid waste and aluminum -based solid waste, stirring Later in the mold to solidify, prepare high -efficiency silicon aluminum -based solid -solid waste gel materials.

Benefits of technology

This method optimizes the effective mix of silicon-aluminum solid waste, improves the reactionability in AAM, makes full use of the silicon-based solid waste, solves the problem of shortage and cost of traditional materials, and improves the gel materials Mechanical strength and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371126A_ABST
    Figure CN119371126A_ABST
Patent Text Reader

Abstract

In order to overcome the defects that in the prior art, when waste glass serves as an alkali activator to excite solid waste, the effect of the waste glass serving as silicon-based solid waste is not fully played, and the recycling amount of the silicon-based solid waste is small, the method for preparing the cementing material from the silicon-aluminum-based solid waste comprises the steps that S1, alkali activator powder and the silicon-based solid waste are evenly mixed, and an alkali activator is prepared; adding water and stirring until the dissolution amount of the active silicon reaches a target value to obtain alkali-activated precursor slurry; s2, adding silicon-based solid waste and aluminum-based solid waste into the alkali-activated precursor slurry, and stirring to obtain alkali-activated solid waste slurry; s3, putting the alkali-activated solid waste slurry into a mold, and curing at 50-70 DEG C for 20-24 hours to obtain a cementing material; the alkali excitation auxiliary agent is NaOH or KOH; the silicon-based solid waste is waste glass and / or quartz tailings; the aluminum-based solid waste is fly ash. The silicon-based solid waste provides active silicon, and the unreacted part has a filling effect, so that the strength of the cementing material is improved, and the silicon-based solid waste is fully utilized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of solid waste recycling, and in particular to a method for preparing a cementitious material from silicon-aluminum-based solid waste. Background Art

[0002] In recent years, aluminosilicate alkali activated materials (AAM) have been gradually regarded as a substitute for traditional Portland cement (OPC) due to their low carbon emissions, excellent mechanical properties and durability.

[0003] The preparation process of AAM includes geopolymerization, involving chemical stages such as dissolution, precipitation, reorganization, gelation and polycondensation. The basic components of AAM are composed of aluminosilicate precursors and alkaline activators: commonly used alkaline activators include sodium hydroxide, potassium hydroxide and sodium silicate; aluminosilicate precursors usually come from natural clays (such as metakaolin) or industrial by-products (such as slag and fly ash). When these precursors are dissolved in alkaline solutions, AAM is formed through a series of chemical reactions.

[0004] However, the shortage and high cost of kaolin, slag and fly ash have forced researchers to look for other aluminosilicate materials to partially or completely replace these traditional materials. Among them, silicon-based waste materials such as waste glass and waste quartz tailings have become a potential precursor material because their composition is similar to that of crystalline materials and they form a disordered structure during the melting process.

[0005] For example, a Chinese patent with publication number: CN 114620965 A proposes an alkali activator dry powder, an alkali-activated cementitious material and a method for preparing an alkali-activated cementitious material. Waste glass is combined with a strong base as an alkali activator to activate solid waste containing silicates and / or aluminosilicates (such as fly ash) to prepare an alkali-activated cementitious material. However, this method has the following defects: the waste glass is only used as an alkali activator material, and the role of the waste glass as a silicon-based solid waste is not fully utilized. In addition, the amount of waste glass added in the cementitious material is relatively small, and it is only used as an auxiliary material for solid waste-based cementitious materials, and the effective recycling amount is small. Summary of the invention

[0006] The present invention overcomes the shortcomings of the prior art that when waste glass is used as an alkali activator to stimulate solid waste to prepare cementitious materials, the role of waste glass as silicon-based solid waste is not fully utilized and the amount of waste glass recycled is small, and provides a method for preparing cementitious materials from silicon-aluminum-based solid waste.

[0007] The technical solution adopted to achieve the above invention object is: a method for preparing a cementitious material from silicon-aluminum-based solid waste, comprising:

[0008] S1. Evenly mix the alkali-activated auxiliary agent powder and silicon-based solid waste, add water under stirring, and continue stirring until the dissolution amount of active silicon reaches the target value to obtain an alkali-activated precursor slurry;

[0009] S2, adding a mixed solid waste containing silicon-based solid waste and aluminum-based solid waste to the alkaline-activated precursor slurry obtained in step S1, stirring, and obtaining an alkaline-activated solid waste slurry;

[0010] S3, placing the alkali-activated solid waste slurry obtained in step S2 in a mold, and curing it at 50-70° C. for 20-24 hours to obtain a gelling material;

[0011] The alkaline excitation auxiliary agent is NaOH or KOH;

[0012] The silicon-based solid waste is: waste glass and / or quartz tailings;

[0013] The aluminum-based solid waste is fly ash.

[0014] The beneficial effects of the present invention are as follows: (1) In the preparation method of the gelling material of the present application, the effective mixing of silicon-based and aluminum-based solid waste polymers is optimized, and silicon-based solid waste is used to replace a large amount of traditional aluminum-based solid waste (fly ash, slag, etc.) AAM precursors, thereby improving their reactivity in AAM;

[0015] (2) In the method of the present application, the silicon-based solid waste is used as an alkali activator to provide active silicon; it is also used as an activated solid waste in the preparation of alkali-activated cementitious materials. The undissolved silicon-based material provides a filling effect in the alkali-activated solid waste slurry to ensure the mechanical strength, working performance, stability and reliable microstructure of the slurry; and in this way, the silicon-based solid waste can be fully utilized, providing a better way for the recycling of silicon-based solid waste, and can also effectively avoid the shortage and high cost caused by the use of kaolin, slag and fly ash.

[0016] (3) The silicon-based solid waste of the present application plays a dual role in AAM, namely, as a silicon source for alkali-activated precursors and a synergistic effect of mechanical filling, so that AAM can achieve ideal performance effects without using sodium silicate while partially replacing the precursor; this method combines the regulation of silicon-aluminum-based solid waste materials with an efficient activation mixing process, aiming to improve the feasibility and final performance of mixed preparation of geopolymers and promote the resource utilization of solid waste.

[0017] (4) In the entire process of preparing cementitious materials, the main raw materials are solid waste, which has lower energy consumption and is green and environmentally friendly. It also avoids the high energy consumption and high carbon emission problems in the production of traditional alkali activator water glass, which is of great significance in promoting the development of low-carbon and environmentally friendly building materials.

[0018] (5) Compared with the traditional alkali activation method, the mixed alkali activation method of the present application is more effective in solidifying and stabilizing heavy metals. After solidification, the concentration of heavy metal leaching is greatly reduced, which reduces secondary pollution and is beneficial to the environment.

[0019] (6) The present application utilizes a mixed alkali activation method to achieve solidification. Compared with the traditional silicon-aluminum activation material, the consolidation strength reaches a similar level, and the setting time can also be controlled within the applicable strength range, which is suitable for large-scale on-site treatment.

[0020] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Attached Figure 1 This is a comparison chart of samples obtained in Examples 1-6 of the present invention. DETAILED DESCRIPTION

[0022] A method for preparing a cementitious material from silicon-aluminum-based solid waste of the present invention comprises the following steps:

[0023] S1. Evenly mix the alkali-activated auxiliary agent powder and silicon-based solid waste, add water under stirring, and continue stirring until the dissolution amount of active silicon reaches the target value to obtain an alkali-activated precursor slurry;

[0024] S2, adding a mixed solid waste containing silicon-based solid waste and aluminum-based solid waste to the alkaline-activated precursor slurry obtained in step S1, stirring, and obtaining an alkaline-activated solid waste slurry;

[0025] S3. Place the alkali-activated solid waste slurry obtained in step S2 in a mold and cure it at 50-70° C. for 20-24 hours to obtain a gelling material.

[0026] In the above preparation method, the alkali activation auxiliary agent is NaOH or KOH; the silicon-based solid waste is: waste glass and / or quartz tailings; and the aluminum-based solid waste is: fly ash.

[0027] Studies have shown that waste glass from different sources affects the reaction characteristics of AAM as well as capillary activity and alkali-silica reaction (ASR). Ground soda-lime glass with a size less than 300 microns can be safely used in concrete, while larger particles of glass may cause expansion reactions due to the presence of microcracks. In order to be able to fully reuse waste glass, in step S1 of the above preparation method, the particle size of the waste glass used is ≤40um, generally 1-40um, and the specific surface area is 1-10cm 2 / g.

[0028] In step S1, the concentration of the alkali-activated auxiliary agent in the alkali-activated precursor slurry is 4-14M. In order to ensure that the amount of active silicon dissolved reaches the available amount, the alkali-activated precursor slurry needs to be continuously stirred until the target amount of active silicon dissolved is obtained, and the target amount of active silicon dissolved is 1 / 20 of the amount of silicon-based solid waste used in step S1. When the alkali-activated precursor slurry is continuously stirred to prepare, the temperature is generally room temperature, but if the target amount of dissolved silicon cannot be achieved at room temperature, a stirring and heating method of 30-50°C can be selected to add the dissolved active silicon.

[0029] The stirring time of the above alkali-activated precursor slurry is determined by the following steps: 3 mL is sampled every 1 hour from the mixed slurry of alkali-activated auxiliary agent powder, silicon-based solid waste and water, oscillated at an oscillation frequency of 110±10 times / min at room temperature for 1 hour, and then allowed to stand for 1 hour; then, a 0.45 um filter membrane is used to filter and collect the leaching solution, and it is refrigerated at 0-4°C for testing; finally, an inductively coupled plasma mass spectrometer is used to analyze the ratio of dissolved Si. When the analysis result is ≥ the target value of the dissolved amount of active silicon, the total stirring time is the stirring time for preparing the alkali-activated precursor slurry.

[0030] In step S2 of the method for preparing the cementitious material of the present application, the ratio of silicon-based solid waste to aluminum-based solid waste is: (4-6):1; the liquid-to-solid ratio of the alkali-activated solid waste slurry is 0.3-0.5. At such a ratio, good processability can be obtained.

[0031] The mass ratio of silicon-based solid waste to aluminum-based solid waste is determined by formula (1):

[0032]

[0033] In formula (1), WS is the liquid-to-solid ratio; m W is the relative water content of the alkali-activated precursor, in ml / g; m NaOH It is the mass of NaOH relative to the alkaline-activated precursor, in g / g.

[0034] The advantages of the preparation method of the cementitious material of the present application are tested through the following examples and comparative examples, wherein waste glass (WGP) is used as silicon-based solid waste, and fly ash (FA) is used as aluminum-based solid waste.

[0035] Pre-treat the waste glass to be used: collect the waste glass and wash it with detergent to ensure that the glass surface does not contain pollutants and impurities. Mechanically crush the washed glass into glass fragments; then use a ball mill to crush the glass fragments to obtain glass powder. Finally, use a laboratory automatic sieving instrument to sieve the glass powder, select the appropriate sieve size, and grade the glass powder to obtain the required micron-grade glass powder. The waste glass is finally ground to a particle size of less than 40um and a specific surface area of ​​1.75cm 2 / g.

[0036] XRF analysis of the fly ash and waste glass used (analysis results are shown in Tables 1 and 2) can be used to obtain their element content and oxide content. Among them, (SiO2+Al2O3+Fe2O3)=91.21%>70% is Class F fly ash, Si and Al are the main element components of fly ash, and the Si / Al molar ratio is 1.16, which is suitable for preparing cementitious materials. The calcium oxide content is 3.53%, which is low-calcium fly ash.

[0037] Table 1. Test results of fly ash composition

[0038] Elements as oxides Wt(%) Elements Wt(%) <![CDATA[SiO2]]> 49.14 Si 22.97 <![CDATA[Al2O3]]> 38.71 Al 20.48 CaO 3.53 Ca 2.52 <![CDATA[Fe2O3]]> 3.36 Fe 2.35 MgO 1.10 Mg 0.66 <![CDATA[TiO2]]> 1.08 Ti 0.43 <![CDATA[SO3]]> 1.02 Sx 0.61 <![CDATA[K2O]]> 0.84 K 0.70 <![CDATA[Na2O]]> 0.40 Na 0.30

[0039] Table 2. Component test results of waste glass

[0040] Elements as oxides Wt(%) Elements Wt(%) <![CDATA[SiO2]]> 71.88 Si 33.60 <![CDATA[Na2O]]> 13.32 Na 9.88 CaO 10.59 Ca 7.57 <![CDATA[Al2O3]]> 1.96 Al 1.04 MgO 0.923 Mg 0.557 <![CDATA[K2O]]> 0.639 K 0.530 <![CDATA[Fe2O3]]> 0.326 Fe 0.228

[0041] In order to evaluate the possibility of using waste glass as a precursor for fly ash-based geopolymers, a systematic study was conducted to prepare polymers by adjusting the precursor ratio under the same concentration of NaOH solution stimulation (maintaining the same alkali concentration as the dissolution experiment). When preparing the neat slurry, only FA was added to Example 1; the WGP:FA of Examples 2, 3, 4, 5, and 6 were 0.35, 1, 2, 4, and 6, respectively, that is, the weight percentage (W / F) of the mixture; and a comparative group 7 was set up at the same time, which was a test piece with water glass added, and the alkali activator modulus was 1 (the specific amount of added materials is shown in Table 3). In addition, the NaOH solution was controlled at 8M, and the liquid-to-solid ratio was fixed at 0.3 to obtain good processability. When preparing the cementitious material, the raw materials were kept under mechanical stirring for 30 minutes to obtain a uniform slurry consisting of partially dissolved glass powder and activated fly ash. The mixture was poured into a polyethylene sealed mold, vibrated for 3 minutes to remove residual air, and then cured in an oven at 60°C for 24 hours to complete the polycondensation reaction.

[0042] Table 3 Material addition amount table of Examples 1-6 and Comparative Example 7

[0043]

[0044]

[0045] The samples of Examples 1-6 are marked as 1-6, and the sample of Comparative Example 1 is marked as 7. The mechanical properties of the above samples were tested by an unconfined compressive strength test (UCS), and the hardening degree of the samples within 7 days and 28 days was recorded. The test results are shown in Table 4.

[0046] Table 4 Hardening degree of samples at 7 days and 28 days (MPa)

[0047]

[0048] From the analysis of Table 4, it can be seen that: (1) when the ratio of silicon-based solid waste to aluminum-based solid waste is 6, the properties of the obtained cementitious material are better, reaching the hardness of the cementitious material when water glass is used as the alkaline activator; (2) the properties of the cementitious material prepared by combining silicon-based solid waste and aluminum-based solid waste are significantly better than those of the cementitious material obtained by using only aluminum-based solid waste (fly ash) as raw material.

Claims

1. A method for preparing a cementitious material from silicon-aluminum-based solid waste, characterized in that: The method for preparing the cementitious material comprises the following steps: S1. Evenly mix the alkali-activated auxiliary agent powder and silicon-based solid waste, add water under stirring, and continue stirring until the dissolution amount of active silicon reaches the target value to obtain an alkali-activated precursor slurry; S2, adding a mixed solid waste containing silicon-based solid waste and aluminum-based solid waste to the alkaline-activated precursor slurry obtained in step S1, stirring, and obtaining an alkaline-activated solid waste slurry; S3, placing the alkali-activated solid waste slurry obtained in step S2 in a mold, and curing it at 50-70° C. for 20-24 hours to obtain a gelling material; The alkaline excitation auxiliary agent is NaOH and / or KOH; The silicon-based solid waste is: waste glass and / or quartz tailings; The aluminum-based solid waste is fly ash.

2. The method for preparing a cementitious material from silicon-aluminum-based solid waste according to claim 1, characterized in that: In the method for preparing the cementitious material, the particle size of the waste glass used is ≤40um and the specific surface area is 1-10cm 2 / g.

3. The method for preparing a cementitious material from silicon-aluminum-based solid waste according to claim 1, characterized in that: In the step S1, the concentration of the alkali-activated auxiliary agent in the alkali-activated precursor slurry is 4-14M.

4. The method for preparing a cementitious material from silicon-aluminum-based solid waste according to claim 1, characterized in that: In the step S1, the target value of the amount of active silicon dissolved is 1 / 20 of the amount of silicon-based solid waste used in the step S1.

5. The method for preparing a cementitious material from silicon-aluminum-based solid waste according to claim 1, characterized in that: In the step S1, the stirring time for preparing the alkali-activated precursor slurry is determined by the following steps: 3 mL of sample is taken from the mixed slurry of alkali-activated auxiliary agent powder, silicon-based solid waste and water every 1 hour, and after oscillation at an oscillation frequency of 110±10 times / min at room temperature for 1 hour, it is allowed to stand for 1 hour; then the leachate is filtered and collected, and refrigerated at 0-4°C for testing; finally, the ratio of dissolved Si is analyzed by inductively coupled plasma mass spectrometry, and when the analysis result is ≥ the target value of the dissolved amount of active silicon, the total stirring time is the stirring time for preparing the alkali-activated precursor slurry.

6. The method for preparing a cementitious material from silicon-aluminum-based solid waste according to claim 1 or 5, characterized in that: In the step S1, the temperature for preparing the alkali-activated precursor slurry is room temperature or a heating condition of 30-50°C.

7. The method for preparing a cementitious material from silicon-aluminum-based solid waste according to claim 1, characterized in that: In the step S2, the liquid-to-solid ratio of the alkali-activated solid waste slurry is 0.3-0.

5.

8. The method for preparing a cementitious material from silicon-aluminum-based solid waste according to claim 1, characterized in that: In the step S2, the ratio of silicon-based solid waste to aluminum-based solid waste is: (4-6):1.

Citation Information

Patent Citations

  • Geopolymer cementing material prepared by replacing alkali activator with waste glass and preparation method of geopolymer cementing material

    CN113845322A

  • Alkali activator dry powder, alkali-activated cementing material and method for preparing alkali-activated cementing material

    CN114620965A

  • Waste glass powder low-carbon cementing material and preparation method thereof

    CN117247241A

  • Manufacturing method of cement zero concrete using mixed waste glass powder and fly ash as binder

    KR1020100037889A

  • Geopolymer cement compositions and methods of making and using same

    WO2015149176A1

Cited By

  • Organic acid excited solid waste-based cementing material

    CN121225897A

  • Organic acid-activated solid waste-based geopolymer

    CN121225897B